Neuroprotective effects of olanzapine against rotenone-induced toxicity in PC12 cells - Xiong Ya-jie; Song Yun-zhen; Zhu Ying; Zuo Wen-qing; Zhao Yi-fan; Shen Xiao; Wang Wen-juan; Liu Ya-li; Wu Jun-chao; Liang Zhong-qin (Acta Pharmacologica Sinica, 2020)
Olanzapine is an antipsychotic drug used to treat patients with schizophrenia due to its lower incidence of extrapyramidal symptoms. Previous studies have shown that olanzapine activates AMP-activated protein kinase (AMPK), and induce autophagy in SH-SY5Y cell line. In this study, we investigated whether olanzapine protected against rotenone-induced neurotoxicity in PC12 cells. We showed that treatment with olanzapine increased the phosphorylation of AMPK in both dose- and time-dependent manners in PC12 cells. In addition, olanzapine activated autophagy and increased autophagic vacuoles. Furthermore, olanzapine pretreatment could protect PC12 cells from rotenone-induced apoptosis. Besides, olanzapine pretreatment could suppress the rotenone-induced depolarization of mitochondrial potential and thus protect the cells. Moreover, pretreatment with speciﬁc AMPK inhibitor compound C or with autophagy inhibitor 3-methyladenine impaired the protective effect of olanzapine on rotenone-treated PC12 cells. In summary, our results show for the ﬁrst time that olanzapine ameliorates rotenone-induced injury by activating autophagy through AMPK pathway.